An in vitro study of the dynamic features of the major histocompatibility complex class I complex relevant to its role as a versatile peptide-receptive molecule - Hörig, Heidi (The National Academy of Sciences of the USA, 1997)
The major histocompatibility complex class I complex consists of a heavy chain and a light chain (β(2)-microglobulin, β(2)m), which assemble with a short endogenously derived peptide in the endoplasmic reticulum. The class I peptide can be directly exchanged, either at the cell surface or, as recently described, in vesicles of the endocytic compartments, thus allowing exogenous peptides to enter the class I presentation pathway. To probe the interactions between the components of the class I molecule, we analyzed the exchange of peptide and β(2)m by using purified, recombinant H2-K(b)/peptide complexes in a cell-free in vitro system. The exchange of competitor peptide was primarily dependent on the off-rate of the original peptide in the class I binding groove. Peptide exchange was not enhanced by the presence of exogenous β(2)m, as exchange occurred to the same extent in its absence. Thus, the exchange of peptide and β(2)m are independent events. The exchange rate of β(2)m also was not affected by the dissociation rates of the original peptides. Furthermore, peptides could substantially exchange into class I molecules over a pH range of 5.5 to 7.5, conditions prevalent in certain endocytic compartments. We conclude that the dynamic properties of the components of class I molecules explain its function as a highly peptide-receptive molecule. The major histocompatibility complex class I can readily receive peptides independent of the presence of exogenous β(2)m, even at a low pH. Such properties are relevant to class I peptide acquisition, which can occur at the cell surface, as well as in specialized endosomes.